P718 Risk and place: the association between hotspot typology and determinants of HIV risk among female sex workers in ukraine. (14th July 2019) - Cheuk, Eve; Leung, Stella; Balakireva, Olga; Pavlova, Daryna; Mcclarty, Leigh; Isac, Shajy; Pickles, Michael; Mishra, Sharmistha; Forget, Evelyn; Lorway, Robert; Sandstrom, Paul; Blanchard, James; et al.
Abstract : Background: The environmental contexts and interactions between people within that environment impact a female sex worker's (FSW) individual behaviour and likelihood of HIV acquisition. Understanding how the environment shapes HIV risk can provide important information for HIV prevention programs that go beyond behaviour-based interventions and address more distal factors contributing to HIV risk among FSWs. Methods: A cross-sectional survey was conducted among FSWs in Dnipro, Ukraine between September 2017 and January 2018. 560 FSWs aged ≥14 years were recruited from "hotspots" (locations where FSWs meet clients). We compared determinants of HIV risk between six hotspot typologies (e.g., brothels, home-based, massage parlours, bars/restaurants, parks, highways) using chi-squared tests. Results: Age at start of sex work (p<0.001), client volume (p<0.001), and HIV testing in the past year (p<0.001) all differed significantly across hotspot typologies. Mean age at start of sex work was oldest for FSWs recruited from highways (24.1 years) and youngest for FSWs recruited from massage parlours (19.8 years). FSWs from highways had the most clients in the past 30 days (mean 22.1 clients) while those from parks had the fewest (mean 17.5 clients). HIV testing in the past year was the most frequent among FSWs from brothels (mean 2.1 times), followed by home-based (1.8 times), massage parlours (1.1 times), highways (1.0 time), bars/restaurants (0.6 times) and parks (0.4 times). The prevalence of physical and sexual violence perpetrated by clients in the past 3 months was 4.3% and 1.6% overall. Compared to women from other hotspot typologies, the proportion of FSWs from highways who reported experience of physical and sexual violence by clients were highest (26.7% and 10.0%). Conclusion: Understanding the association between HIV risk factors and hotspot typology can help HIV prevention programs tailor interventions, and target linkage and delivery of services to the relevant subgroups of a key population. Disclosure: No significant relationships.